Aging-related changes in neuroimmune-endocrine function: Implications for hippocampal-dependent cognition - Barrientos, Ruth M. (2012)
Healthy aged individuals are more likely to suffer profound memory impairments following a challenging life event such as a severe bacterial infection, surgery, or an intense psychological stressor, than are younger adults. Importantly, these peripheral challenges are capable of producing a neuroinflammatory response, (e.g., increased pro-inflammatory cytokines). In this review we will present the literature demonstrating that in the healthy aged brain this response is exaggerated and prolonged. Normal aging primes or sensitizes microglia and this appears to be the source of this amplified response. We will review the growing literature suggesting that a dysregulated neuroendocrine response in the aged organism is skewed towards higher brain CORT levels, and that this may play a critical role in priming microglia. Among the outcomes of an exaggerated neuroinflammatory response are impairments in synaptic plasticity, and reductions in key downstream mediators such as Arc and BDNF. We will show that each of these mechanisms is important for long-term memory formation, and is compromised by elevated pro-inflammatory cytokines.